PERCEPTIONS OF INTERNATIONAL STUDENTS ON SERVICE QUALITY DELIVERY - Esmati, Shahabuddin (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2024)
This study aims to explore international students' perceptions on the service quality delivery at Universitas Hasanuddin. The method used is a qualitative approach with in-depth interview techniques. Data was collected through interviews with the international students under the KNB scholarships, who were studying Indonesian language through BIPA program at Unhas. Interviews were conducted using a semi-structured interview guide which allowed researchers to explore participants' experiences and views in more depth. The findings of the study show that international students have varying perceptions of the quality of service they receive, with the majority assessing aspects of academic services, administration and campus facilities as quite adequate. However, there are several challenges related to communication, cultural understanding, and support in social and academic adaptation. This research recommends improving coordination between various parties at universities to improve services and better meet the needs of international students. It is hoped that these findings can become a reference for university administrators in designing policies that are more responsive to the needs of international students.